Gender and Ethnicity-Married immigrants in Britain - Christian Dustmann; Francesca Fabbri (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2005)
In this paper we investigate economic activity of female immigrants and their husbands in Britain. We distinguish between two immigrant groups: foreign born females who belong to an ethnic minority group and their husbands, and foreign born females who are white and their husbands. We compare these to native born white women and their husbands. Our analysis deviates from the usual mean analysis and investigates employment, hours worked and earnings for males and females, as well as their combined family earnings, along the distribution of husbands' economic potential. We analyse the extent to which economic disadvantage may be reinforced on the household level. We investigate to what extent disadvantage can be explained by differences in observable characteristics. We analyse employment assimilation for all groups over the migration cycle. Our main results are that white female immigrants and their husbands are quite successful, with an overall advantage in earnings over white native born both individually and at the household level. On the other hand, minority immigrants and their husbands are less successful, in particular at the lower end of the husband's distribution of economic potential. This is mainly due to low employment of both genders, which leads to disadvantage in earnings, intensified at the household level. Only part of this differential can be explained by observable characteristics. Over the migration cycle, the data suggests that employment differentials are large at entry for white immigrant females, and even larger for minority females, but the gap to the native born closes. Assimilation is more rapid for white females.
Keywords: 330; Migration; Ethnicity; Attitudes